NILAI-NILAI AKHLAK SOSIAL DALAM PERSPEKTIF HADIS NABI SAW - Siti Nurhalijah; Muhammad Alif (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2026)
Social morality constitutes a fundamental aspect of Islamic teachings and is tightly linked to the level of communal life. From the perspective of the Prophet Muhammad’s (peace be upon him) hadith, social morality is not merely understood as interpersonal ethics, but as a manifestation of faith embodied in attitudes, behaviors, and social concern. This research intends to explore the classification and application of ethical social values through the lens of the Prophet’s hadith as a basis for establishing a cohesive, civilized, and sustainable society. The research questions address how the Prophet’s hadith views social moral values and how these values can be classified through the thematic hadith method and content analysis. The project engages a qualitative approach using the thematic hadith method (al-ḥadīṡ al-mawḍū‘ī) combined with content analysis based on grounded theory. The research data are derived from hadiths relevant to the theme of social morality sourced from major hadith collections, supported by related scholarly literature. The findings indicate that social moral values in hadith can be classified into three main themes: the theological foundations of social morality, forms of social morality, and their relevance in contemporary life. The discussion emphasizes that social morality has a crucial urgency as an ethical guideline in responding to the challenges of modern life characterized by individualism and the weakening of social solidarity. This study concludes that social moral values in the Prophet’s hadith are applicable, timeless, and essential to be continuously internalized in social life.